The prevalent factors of anxiety in women undergoing mammography - Jaafar Sidek, Mohamed Ariff; Amajid, Kanchlla; Loh, Yi Sheng; Rosli, Muhammad Ariff; Hashim, Iffah Syahirah; Mohd Suffian, Nur Ashiqin; Abdullah, Norlia; Midin, Marhani (Frontiers in Psychiatry, 2023)
Background: Breast cancer is the most common cancer among women in Malaysia. Anxiety is one factor that deters women from participating in mammography. This study aimed to assess the anxiety level and its associated factors in women undergoing mammography Methods: A three-month cross-sectional study was conducted using self-administered questionnaires, encompassing socio-demographic details, clinical characteristics, and the State-Trait Anxiety Inventory.The mean age of the participants was 57 years old (SD ±10.098). Repeat mammograms consisted of 48.8% of the participants. One-third (35.7%) of them had a history of breast disease. Most participants (84.5%) did not have a positive family history of breast cancer. The proportion of participants with moderate and high anxiety levels was 41.8%. The cause of anxiety was mainly due to the fear of the results (69%), while familiarity with the procedure reduced anxiety among respondents. Socio-demographic and clinical factors were not significantly associated with anxiety levels. However, a statistically significant positive correlation was found between state and trait anxiety scores (r = 0.568, p = 0.001, n = 213).The urban setting and absence of questions on the location of origin in the study may have excluded data from the rural population. This may have prevented a true representation of the Malaysian population.The findings suggest a better understanding of the procedures involved as well as the subsequent disease management would be beneficial in alleviating anxiety prior to, during, and postmammogram.